FDI stocks are a biased measure of foreign affiliate activity - Sjoerd Beugelsdijk; Jean-François Hennart; Arjen Slangen; Roger Smeets (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2011)
Researchers often call the value added (VA) in a host country by firms based in another country foreign direct investment (FDI) and use FDI stocks and flows from a country's balance of payments to measure it. Because FDI stocks and flows only measure the financial flows between parents and their foreign affiliates, excluding locally raised funds, and because they omit the contribution of local labor to affiliate VA, they systematically underestimate that VA in more developed countries and thus are a biased measure of multinational activity.
Keywords: 330